2013
DOI: 10.1302/0301-620x.95b10.31477
|View full text |Cite
|
Sign up to set email alerts
|

Restoring the anatomical tibial slope and limb axis may maximise post-operative flexion in posterior-stabilised total knee replacements

Abstract: The optimal management of the tibial slope in achieving a high flexion angle in posterior-stabilised (PS) total knee replacement (TKR) is not well understood, and most studies evaluating the posterior tibial slope have been conducted on cruciate-retaining TKRs. We analysed pre- and post-operative tibial slope differences, pre- and post-operative coronal knee alignment and post-operative maximum flexion angle in 167 patients undergoing 209 TKRs. The mean pre-operative posterior tibial slope was 8.6° (1.3° to 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Further insight came from Singh et al (2013), who suggested that re-creation of the anatomical tibial slope appears to improve maximum flexion in a study of 209 posterior-stabilized (PS) TKAs. Under no circumstances should the proximal tibia be cut with an anterior slope, as it would lead to impaired posterior flexion space and possible instability (Waelchli and Romero 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further insight came from Singh et al (2013), who suggested that re-creation of the anatomical tibial slope appears to improve maximum flexion in a study of 209 posterior-stabilized (PS) TKAs. Under no circumstances should the proximal tibia be cut with an anterior slope, as it would lead to impaired posterior flexion space and possible instability (Waelchli and Romero 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The tibial component should be placed in neutral coronal alignment (90°) with maximum bone coverage and minimal if any overhang (Berend et al 2004, Bonner et al 2011, Ritter et al 2011, Kim et al 2014). In the sagittal plane, the femoral component should be placed with 0–3° of flexion, and the tibial slope should be 0–7° (In et al 2009, Lustig et al 2012, Kim et al 2014, Singh et al 2013). Internal rotation of the femoral component with respect to sTEA should be avoided, as the femoral component should be placed in 2–5° of external rotation in relation to sTEA (Akagi et al 1999, Matsuda et al 2001, Kim et al 2014, Bell et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…To a clinically acceptable range, we set the three levels of varus angle of the tibial prosthesis as − 3°, 0°, + 3°in the orthogonal experimental design in this study. Some studies showed that the maintenance of 0-7°posterior tibial slope in the sagittal plane was beneficial for the long-term stability of the prosthesis [26,27]. The tibial posterior slope angle of our volunteer was 4°, and the tibial prosthesis selected in our study had its own inherent 3°posterior slope angle, so we set the three levels of the posterior slope angle of the tibial prosthesis in our orthogonal experimental design as 1°, 2°, and 3°.…”
Section: Discussionmentioning
confidence: 99%
“…2 Studies on the natural history of FFD postoperatively revealed a tendency for majority of the FFD to increase in the early post-operative period and then decrease, followed by a gradual improvement in knee movement with time. 4,[10][11][12][13][14][15][16] However, there still exist a proportion of these patients with persistent FFD that might require surgical correction, and arthrofibrosis involving excessive post-operative scarring is regarded as the most unresponsive cause of FFD. 2 Here, we then analysed the predictive factors of these persistent FFD at the 24-month post-operative time point.…”
Section: Discussionmentioning
confidence: 99%